Evaluation of increasing select menhaden fish meal or peptone protein sources in nursery pig diets - A J Myers; B W Ratliff; D McKilligan; G Xu; J Moline; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2010)
A total of 350 nursery pigs (PIC 1050 x C327, initially 14.3 lb and 28 d of age) were used in a 24-d study to evaluate the effects of select menhaden fish meal (SMFM), PEP2 (also known as Ferm-O-Tide), and Peptone 50, on nursery pig performance. PEP2 and Peptone 50 are a combination of refined porcine intestinal mucosa that is co-dried with vegetable proteins. PEP2 contains an enzymatically processed vegetable protein, while Peptone 50 contains a complementary vegetable protein. There were 10 dietary treatments: a negative control containing no specialty protein, the negative control diet with 2, 4, or 6% SMFM, the negative control diet with 2, 4, or 6% PEP2, or the negative control diet with 2, 4, or 6% Peptone 50. A common pretest diet was fed in pellet form for the first 6 d postweaning. Experimental diets were fed in meal form from d 0 to 14 and a common diet was fed from d 14 to 24. From d 0 to 7, there were no differences among treatments for ADG. Pigs fed diets containing PEP2 had greater (P<0.03) ADFI compared with pigs fed diets containing SMFM and Peptone 50. From d 7 to 14, increasing PEP2 or SMFM increased (quadratic; P<0.04) ADG, but there were no differences between pigs fed the two protein sources. Also during this period, pigs fed increasing PEP2 had increased (P<0.02) ADFI compared to pigs fed SMFM or Peptone 50. In addition, as PEP2 increased from 2 to 4% ADFI increased (quadratic; P<0.01). In Phase 2, pigs previously fed Peptone 50 had decreased (P<0.05) ADG compared to pigs previously fed diets containing SMFM. Overall, pigs fed PEP2 had greater (P<0.02) ADFI compared to pigs fed Peptone 50. In addition, pigs fed PEP2 had improved (P<0.03) F/G compared to pigs fed SMFM. Finally, increasing PEP2 improved (quadratic; P<0.04) F/G, with the most improvement seen in pigs fed the 6% PEP2 diets. These results suggest that PEP2 or Peptone 50 are suitable replacements for SMFM.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Fish meal; PEP2; PEP50